Effect of inhaled terbutaline on substrate utilization and 300-kcal time trial performance - Kalsen, A.; Hostrup, M.; Karlsson, S.; Hemmersbach, P.; Bangsbo, J.; Backer, V. (Journal of Applied Physiology, 2014)
In a randomized, double-blind crossover design, we investigated the effect of the beta2-agonist terbutaline (TER) on endurance performance and substrate utilization in nine moderately trained men [maximum oxygen uptake (VO2 max) 58.9 ± 3.1 ml/min·kg]. Subjects performed 60 min of submaximal exercise (65-70% of VO2 max) immediately followed by a 300-kcal time trial with inhalation of either 15 mg of TER or placebo (PLA). Pulmonary gas exchange was measured during the submaximal exercise, and muscle biopsies were collected before and after the exercise bouts. Time trial performance was not different between TER and PLA (1,072 ± 145 vs. 1,054 ± 125 s). During the submaximal exercise, respiratory exchange ratio, glycogen breakdown (TER 266 ± 32, PLA 195 ± 28 mmol/kg dw), and muscle lactate accumulation (TER 20.3 ± 1.6, PLA 13.2 ± 1.2 mmol/kg dw) were higher (P < 0.05) with TER than PLA. There was no difference between TER and PLA in net muscle glycogen utilization or lactate accumulation during the time trial. Intramyocellular triacylglycerol content did not change with treatment or exercise. Pyruvate dehydrogenase-E1a phosphorylation at Ser293 and Ser300 was lower (P < 0.05) before submaximal exercise with TER than PLA, with no difference after the submaximal exercise and the time trial. Before submaximal exercise, acetyl-CoA carboxylase 2 (ACC2) phosphorylation at Ser221 was higher (P < 0.05) with TER than PLA. There was no difference in phosphorylation of alpha 5'-AMP-activated protein kinase (aAMPK) at Thr172 between treatments. The present study suggests that beta2-agonists do not enhance 300-kcal time trial performance, but they increase carbohydrate metabolism in skeletal muscles during submaximal exercise independent of AMPK and ACC phosphorylation, and that this effect diminishes as drug exposure time, exercise duration, and intensity are increased.